The Elasticities of Complementarity and Substitution - Peter Broer (Tinbergen Institute, 2004)
This paper argues that the conventional definition of the elasticity of complementarity is not well suited to deal with the case of increasing returns. It proposes a slightly different formula, that uses a distance function formulation instead of a production function. The proposed definition coincides with the Hicksian measure in case the production function displays constant returns. It is more informative in case returns to scale are not constant, as it disentangles entry effects and substitution effects of factor supplies. The new definition is also preferable in that it is fully symmetric with the definition of the elasticity of substitution.
Keywords: D21; D43; L16; 330; distance function; elasticity of complementarity; returns to scale; tangency condition; Substitutionselastizität; Skalenertrag; Theorie